Effect of plant bioregulators on the vase life of snapdragon (Antirrhinum majus) cut flowers - PERINBAN, SELLAM; MAJUMDER, JAYOTI; RAI, PUJA; SINGH, BABITA (The Indian Journal of Agricultural Sciences, 2015)
The present study on effect of plant bioregulators on the vase life of snapdragon (Antirrhinum majus L) cut flowers was conducted at Directorate of Floricultural Research, Pusa Campus, New Delhi during 2013-14 to evaluate snapdragon flower spikes as cut flower based on vase life and the effect of plant bioregulators on the vase life of snapdragon flower. Plant bioregulators namely aminooxyacetic acid (AOA) 0.5mM, salicylic acid (SA) 1mM and benzyl adenine (BA) 0.2mM along with 2% sucrose was evaluated. Vase life of snapdragon flower spikes were significantly increased in treatments with plant bio regulators BA+ sucrose, SA + sucrose and AOA + sucrose (9.3, 9 and 8.3 days) in comparison with control (5.6 days) and sucrose (2%) alone (7.3days). Treatments with plant bioregulators delayed the flower opening and flower senescence. Change in fresh weight was less in treatments with plant bioregulators and vase solution uptake rate was also more in the same treatments when compared to Control. Membrane stability index of spikes treated with BA + sucrose was better (64.99%) after 9 days of experiment. Bract chlorophyll content and petal carotenoid content after 9 days of vase life were found better in BA+ sucrose treatment (3.2 mg/g and 0.896 mg/ g/respectively). BA performed better than other bio regulators in terms of vase life, colour retention and membrane stability. Sucrose (2%) alone improved the vase life but not significant when compared with solutions containing plant growth regulators along with it.